Kokemuksia mielisairaalasta Muistoihin kaivertuneet tilat - Jäntti, Saara; Heimonen, Kirsi; Kuuva, Sari; Maanmieli, Karoliina; Rissanen, Anu (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2022)
Finnish psychiatric practice has been heavily based on institutionalization, and mental hospitals have played important cultural and historical roles in Finland. Our multidisciplinary research focuses on the bodily, spatial, affective, and multisensory aspects of the memories of patients, relatives, staff, and their children. The memories were collected and archived in the Finnish Literature Society in 2014-2015. These 92 written pieces cover the period from the 1930s to the 2010s. They reflect significant changes in Finnish psychiatry and provide crucial insights into the various meanings of mental hospitals in people's lives, and the social and cultural forces that shape attitudes to and ideas about mental health problems, psychiatric care, and service users today. Drawing on our backgrounds in history, artistic research, and visual, cultural and literary studies, we provide new ways of reading and interpreting the memories and experiences in psychiatry. The study discusses memory, mental hospitals as lived spaces, the history of Finnish psychiatry and the relation between the memories of the different groups of writers. The chapters approach memories from the perspectives of affects and atmospheres, violence and abuse, everyday life at the hospital in the 1930s, feelings of fear and safety in the memories of the children of the staff, and the historically and culturally contingent tensions between hospitals and homes.